Comparison of alternative full and brief versions of functional status scales among older adults in China. - Jeremy Reich; Mark G Thompson; Benjamin J Cowling; A Danielle Iuliano; Carolyn Greene; Yuyun Chen; Rachael Phadnis; Nancy H L Leung; Ying Song; Vicky J Fang; Cuiling Xu; Qigang Dai; et al. (PLoS ONE, 2020)
Background Brief assessments of functional status for community-dwelling older adults are needed given expanded interest in the measurement of functional decline. Methods As part of a 2015 prospective cohort study of older adults aged 60-89 years in Jiangsu Province, China, 1506 participants were randomly assigned to two groups; each group was administered one of two alternative 20-item versions of a scale to assess activities of daily living (ADL) and instrumental activities of daily living (IADL) drawn from multiple commonly-used scales. One version asked if they required help to perform activities (ADL-IADL-HELP-20), while the other version provided additional response options if activities could be done alone but with difficulty (ADL-IADL-DIFFICULTY-20). Item responses to both versions were compared using the binomial test for differences in proportion (with Wald 95% confidence interval [CI]). A brief 9-item scale (ADL-IADL-DIFFICULTY-9) was developed favoring items identified as difficult or requiring help by ≥4%, with low redundancy and/or residual correlations, and with significant correlations with age and other health indicators. We repeated assessment of the measurement properties of the brief scale in two subsequent samples of older adults in Hong Kong in 2016 (aged 70-79 years; n = 404) and 2017 (aged 65-82 years; n = 1854). Results Asking if an activity can be done alone but with difficulty increased the proportion of participants reporting restriction on 9 of 20 items, for which 95% CI for difference scores did not overlap with zero; the proportion with at least one limitation increased from 28.6% to 34.2% or an absolute increase of 5.6% (95% CI = 0.9-10.3%), which was a relative increase of 19.6%. The brief ADL-IADL-DIFFICULTY-9 maintained excellent internal consistency (α = 0.93) and had similar ceiling effect (68.1%), invariant item ordering (H trans = .41; medium), and correlations with age and other health measures compared with the 20-item version. The brief scale performed similarly when subsequently administered to older adults in Hong Kong. Conclusions Asking if tasks can be done alone but with difficulty can modestly reduce ceiling effects. It's possible that the length of commonly-used scales can be reduced by over half if researchers are primarily interested in a summed indicator rather than an inventory of specific types of deficits.